Management information systems: a complete text book including solved cases - Oka, Milind M (Everest publishing house, 2000)
Management information systems: a complete text book including solved cases / Oka, Milind M. -- Pune: Everest publishing house, 2000 658.4038 Ok41e7 7th ed. No. of Copies : 1